Design, Expression, and Inhibitory Effects of Antagonistic Single-Chain Platelet-Derived Growth Factor on Lung Cancer Cells - Salim Alhafyan (Syrian Journal for Science and Innovation)
Platelet-derived growth factor (PDGF) plays a pivotal role in numerous physiological and pathological conditions, acting as a dimeric disulfide-bound protein that induces receptor dimerization and subsequently activates cell signaling pathways. Given its involvement in various malignant and benign diseases, targeting the PDGF signaling pathway is a promising therapeutic strategy. In this study, a single-chain antagonist PDGF (sc-PDGF) was designed by leveraging structural insights from the PDGF BB/receptor complex (PDB ID: 3JMG). The design involved substituting a receptor-binding site in one pole while keeping the other intact. Molecular dynamics simulations of the designed antagonistic sc-PDGF showed a noteworthy reduction in binding affinity at the mutant interface, indicating a reduced capability to effectively bind the receptor. The antagonistic sc-PDGF was successfully expressed in Escherichia coli, purified, and refolded using a one-step affinity chromatography approach. Far-UV circular dichroism spectroscopy demonstrated no significant alterations in the secondary structure of the designed sc-PDGF. Additionally, MTT assays confirmed the inhibitory effect of the sc-PDGF on lung cancer cells (A549), with an IC50 value of 0.72 µg/ml. This result underscores the potential of the sc-PDGF antagonist as a viable drug candidate for suppressing the proliferation of cancer cells, particularly those in which PDGF plays a critical role in cell growth.